STRUCTURAL AND SEMANTIC FEATURES OF FEMINISTIC LEXICOLOGY AND TRANSLA TIONAL PROBLEMS (IN THE EXAMPLE OF O' TKAN KUNLAR BY A. KODIRI HEROINE KUMUSH AND GONE WITH WIND M.MITCHELL HEROINE SCARLET - Tokhirova Dilbahor Normurodovna (Western European Studies, 2025)
The paper examines the structural and semantic features of feministic lexicology in the novel s O'tkan Kunlar by A. Kodiri, focusing on the heroine Kumush,and Gone with the Wind by M. Mitchell, focusing on the heroine Scarlett.Special attention is given to the lexical represe ntation of female characters,their emotional and social spheres, and the specific vocabulary t hat reflects their worldview, roles, and identity. The study analyzes difficulties and challenge s in translating feministic lexical units from Uzbek and English into other languages,taking i nto account cultural and contextual factors. The research highlights the correlation between t he semantic richness of feministic vocabulary and the translation problems arising from struc tural and stylistic differences in the source and target languages. Practical implications conce rn translators, literary scholars,and students of comparative literature.
Keywords: Feministic lexicology; lexical-semantic features; translation problems